Neonatal outcome in pregnancies complicated by Gestational Diabetes Mellitus in a tertiary care hospital from South India - Jamdade, Shrikant; Mitra, Nibedita; V, Senthilkumar; G, Kavitha; M, Nithya (Asian Journal of Medical Sciences, 2022)
Background: Affecting 537 million adults worldwide and counting, diabetes is spiraling out of control. Historically pregnancies complicated by abnormal glycemic control are associated with various neonatal complications, increased morbidity and mortality. Majority of abnormal glycemic control in pregnancy is attributed to Gestational Diabetes Mellitus (GDM) rather than pregestational Diabetes Mellitus. 21 million live births (1 in 6) were affected by hyperglycemia during pregnancy worldwide in 2021, approximately 80% of which is attributed to GDM. With disease burden increasing at an alarming rate a hospital-based descriptive study was conducted to observe neonatal outcome in pregnancies complicated by GDM. Aims and Objectives: The present study was undertaken to observe neonatal outcome, in pregnancies complicated by GDM in terms of neonatal mortality and neonatal complications, in the study hospital. Materials and Methods: 115 mothers diagnosed to have GDM and their infants were enrolled in the study. Maternal antenatal records and indoor case sheets were used to collect data regarding maternal medical profile and any associated obstetric complications. Neonatal indoor case sheets were reviewed to collect data regarding gestational age, birth weight, and gender. Neonatal complications and mortality if any were recorded. Descriptive analysis was done using data collected. Results: Out of 115 infants 60 (52.2%) were female and 55 (47.8%) were male, 108 (93.9%) were full term and 7 (6.1%) were preterm. 93 (80.9%) infants were appropriate for gestational age, 15 (13.0%) were small for gestational age, and 7 (6.1%) were large for gestational age. Four (3.4%) infants had birth weight more than 4000 g. Neonatal complications were noted in 26 (22.6%) infants, most common being neonatal hyperbilirubinemia (n=14) (12.2%). Other neonatal complications observed were respiratory distress (n=5) (4.3%), perinatal asphyxia (n=3) (2.6%), hypoglycemia (n=2) (1.7%), meconium aspiration syndrome (n=1) (0.9%), and neonatal convulsions (n=1) (0.9%). Cardiac malformations noted were ventricular septal defect (n=1) (0.9%) and atrial septal defect (n=1) (0.9%). There was no neonatal mortality noted in the study. Conclusion: In our study, we observed a better neonatal outcome in terms of neonatal mortality and morbidity as compared to that noted historically in the literature. Early detection and meticulous maternal diabetes management is associated with better neonatal outcome as observed in this study. This observation is also well supported in the literature along with the fact that, untreated GDM is associated with significant neonatal morbidity.